Community use of systemic antibiotics among individuals aged 15 and over in Brazil: A seven-year population-based cross-sectional study - Tatiana de Jesus Nascimento Ferreira; Rosângela Caetano; Ria Benkö; João Henrique de Araújo Morais; Claudia Garcia Serpa Osorio-de-Castro (PLoS ONE, 2025)
Brazil is recognized as the largest consumer of antibiotics among Latin American countries, despite the implementation of restrictive measures since 2011. Systemic antibiotics (J01) are commonly prescribed for community use and empirically for treating viral diseases, which can result in therapeutic failure and potential sources of microbial resistance. Studying the use of J01 at the outpatient and community level provides an opportunity to understand different clinical and social perspectives on the use of these drugs. The study aimed to describe the consumption of J01 in young people and adults in Brazil, based on dispensing from private community pharmacies. We conducted a cross-sectional study using data from January 2014 to December 2020, extracted from dispensing records in the National System for the Management of Controlled Products at the national, regional, and state levels. The primary consumption indicator used was the Defined Daily Dose per 1,000 inhabitants per day (DID). A total of 259,313,837 antibiotic dispensing records were collected during the period. Of this total, 67.2% were J01 and complied with other inclusion criteria established for the analysis. Over the period, 4,590,329,296 standard units were consumed in Brazil, characterized by a non-linear trend (p-value 0.357). Consumption ranged from 9.8 to 12.9 in DID. Penicillins (J01C) and macrolides (J01F) were the most consumed therapeutic groups, accounting for 28.1% and 28.6% of total J01 consumption, respectively, in terms of median usage. The analysis revealed that although overall consumption is increasing across the country, the patterns differ based on the distribution of dispensing records and DID values in various states. The results provide insights that can serve as a foundation for local health managers to analyze and interpret the data, promoting the development of surveillance and monitoring strategies for the use of J01.